Dandelion Effect on Broiler Representation - GalibA.M.Al-Kassie; Mamdooh A.M.Al-Nasrawi; Nihad Abdul Lateef Ali (Indian Journal of Forensic Medicine & Toxicology, 2021)
The aim of this study was to evaluate the dandelion as a source of probiotic. 300 day old chicks (Hubbardtype) were chosen for this experiment. The results showed significant effect (p=0.05) for chicks fed withdifferent levels of dandelion. 1.00% level shows the highest weight gain, not effects on eatable incentive inspite of there is found simple calculated of treatment significant effect (p=0.05). The study concluded thatusing dandelion fed as additive at 1.00% promote the performance of the whole chicks during the breadedchicks.